PENGENALAN CERITA MITOLOGI MAKASSAR: LEGENDA PENJAGA TAHTA KEMBAR MELALUI BUKU DIGITAL ILUSTRASI KYRAN - Shabiriani, Uzda Nabila; Retanubun, Immanuel Sean Keane (Universitas Mercu Buana, 2024)
Sulawesi Island is rich in myths, one of which is the legendary tale from Makassar City. This research underlines the Legend of the Twin Thrones, a story about Suri Pa'langi, a warrior chosen by the twin spirits of Gowa and Tallo to protect Makassar from the threat of a portal that releases monsters. The story seamlessly interweaves historical fragments of the Gowa-Tallo Kingdom and fantasy in order to construct an interesting plot that reflects Makassar's cultural unity. Further, it is intended that the development of the Digital Illustrated Book